Enviroment Knowledge Implementation to Senior High School and Collage Students Activities - Nita Noriko (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2019)
Abstract - Al Qur’an is the word of Allah SWT as the rules and guidance to get harmony and success life in here and after. The explanation and ways how to implement command of Al Qur’an are found in Al Hadist Muhammad SAW. Al Qur’an teaches may aspect of life and one of them is how using and managing the natural resources and conserve of environment, using the source of energy, water, health and sanitation. In the other hand the people of the world included Indonesia facing environment problem. Sustainable Development Goals (SDGs) from United nation are collected of 17 global goal or agenda 2030 for transforming our world 2030 and containing strategy to solve environment problem. Base on the fact, the problem is how awareness the senior high school and higher education (university) students specially Islamic students to contribute conserve the environment?. The goals of the research were to know how environment awareness and action performance of students from senior high school and university. Methodology of the research was survey and observation concerning in 320 student from 4 senior high schools and in 1 university. The result of the research showed 41,5% of natural and 40.35% social science students from Islamic values senior high schools (SMAI IPA and IPS) showed the awareness action to environment. In SMAN IPA students showed their awareness 51.1% and SMAN IPS 20.6% Based on observation students from university with Islamic values showed low awareness of environment.  Keyword - Al Qur’an, Awareness, Environment, Hadist, Students